FRI0052 Variations in Disease Activity and Therapeutic Management of Rheumatoid Arthritis in Different International Regions: A Comparison of Data from the Corrona International and Corrona US Registries. (10th June 2014) - Pappas, D.A.; Lampl, K.; Kremer, J.M.; Radominski, S.C.; Gal, J.; Nyberg, F.; Malaviya, A.; Whitworth, A.; Rillo, O.; Gibofsky, A.; Popkova, T.; Ho, M.; et al.
Abstract : Background: The CORRONA International (C.Intl) rheumatoid arthritis (RA) registry is a multinational RA registry uniformly collecting baseline and longitudinal data. We explored variations in RA disease activity and drug utilization across regions participating in C.Intl, and CORRONA US (C.USA) RA registries. Methods: The C.Intl registry is a multi-center, observational registry. Adult RA patients (pts) have been enrolled from 83 rheumatology practices in 10 countries in 3 regions: Latin America (LA) (Mexico, Brazil, Argentina), Eastern Europe (EEu) (Poland, Czech Republic, Hungary, Romania, Russia, Ukraine), Asia (India). The C.USA registry enrolls pts from 111 rheumatology practices across the US. Both registries collect data in a similar manner from rheumatologists and RA pts. We present baseline descriptive data across the regions participating in C.Intl, including variations in RA drug utilization, disease activity and functionality. We explored differences stratified by new (≤3 years duration) versus established (3+ years) disease. We compared C.Intl data by region with data from the most recent visit of pts enrolled in C.USA. Results: 5696 pts enrolled in C.Intl and 20, 291 RA pts followed in C.USA were analyzed. Mean (Standard Deviation (SD)) age was highest in the US and lowest in Asia [LA 54.2 years (12.9), EEu 57.1 (12.2), Asia 47.6 (11.9), US 60.3 (12.6)]. The majority of patients were women (LA: 86.7%, EEu: 83.4%, Asia: 85.5%, US: 76.6%). Mean (SD) disease duration was indicative of overall established dx [LA 9.9 years (8.7), EEu 9.1 (8.6), Asia 6.3 (5.8), US 12 (10.1)]. The majority of pts were seropositive (LA 83.5%, EEu 76.4%, Asia 65.4%, US 76%). Disease activity was higher, functionality worse, but biologic drug utilization and narcotic pain medication use were lower, in C.Intl regions compared to C.USA (Table 1 ). Conclusions: There are regional differences in disease activity, functionality, and management of RA, which may be influenced by variations in demographic and genetic backgrounds of pt populations, prescribing patterns of local physicians and differences in standard of care. Acknowledgements: This study is sponsored by CORRONA. Initial funding for the CORRONA International was provided by AstraZeneca. In the last two years, AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Lilly, Novartis, Pfizer, Savient, Vertex, and UCB have supported CORRONA through contracted subscriptions. Disclosure of Interest: D. Pappas Employee of: CORRONA, Inc., Paid instructor for: Novartis, K. Lampl Shareholder of: AstraZeneca, Employee of: AstraZeneca, J. Kremer Shareholder of: CORRONA, Inc., Employee of: CORRONA, Inc., S. Radominski Grant/research support: Pfizer, BMS, AstraZeneca, Amgen, Sanofi, Novartis, Celltrion, Roche;, Consultant for: Pfizer, BMS, AstraZeneca, Employee of: Universidade Federal do Parana- Curitiba- Brzazil;, Speakers bureau: Pfizer, BMS, AstraZeneca, Janssen, Sanofi, GSK, J. Gal: None declared, F. Nyberg Shareholder of: AstraZeneca, Employee of: AstraZeneca, A. Malaviya Consultant for: Part-time Consultant Rheumatologist at ISIC Hospital, Advisory Board Member Janssen Pharma, Roche Pharma, Pfizer Pharma, Sanofi Pharma, A. Whitworth Employee of: CORRONA, Inc., O. Rillo: None declared, A. Gibofsky Shareholder of: Amgen, BMS, GlaxoSmithKline, Johnson & Johnson, Pfizer, Roche, Consultant for: Amgen, AstraZeneca, Celgene, Horizon, Iroko, Pfizer, Roche, Antares, UCB, Speakers bureau: Amgen, Pfizer, Roche, UCB; Stockholder, T. Popkova Speakers bureau: GlaxoSmithKline, MSD, AstraZeneca, M. Ho Employee of: AstraZeneca, I. Laurindo Consultant for: Abbott, AstraZeneca, Bristol, Janssen, Pfizer, Speakers bureau: Abbott, AstraZeneca, Bristol, Janssen, Pfizer, Roche, G. Reed Employee of: CORRONA, Inc., E. Kerzberg: None declared, L. Horne Shareholder of: AstraZeneca, Employee of: AstraZeneca, R. Zahora: None declared, K. Saunders Employee of: CORRONA, Inc., B. Pons-Estel Grant/research support: GLADAR, ABBOTT Laboratories, A. Onofrei Employee of: UMASS Medical School, J. Greenberg Shareholder of: CORRONA, Inc., Consultant for: AstraZeneca, Pfizer, Employee of: CORRONA, Inc. DOI: 10.1136/annrheumdis-2014-eular.1692